Island of the Blue Dolphins - O'Dell, Scott, 1898-1989 (Boston : Houghton Mifflin Company, 1960)
The gripping story of young Karana, an Indian girl who survives by herself for eighteen years on a deserted island off the California coast. A quiet acceptance of fate characterizes her ordeal.
Inspired by the life of the'Lone Woman of San Nicolas'whose remains were baptized conditionally in 1853 by Father Gonzales Rubio as Juana Maria.
Keywords: Juana Marie, -- -1853 -- Juvenile fiction; Indians of North America -- California -- Channel Islands -- Juvenile fiction; Islands -- Juvenile fiction; Islands -- Juvenile fiction